A survey of abandonment of student nurses at Greys Hospital - S.F. Fry; A. Karani; G.M. Tuckell (AOSIS, 1982)
In all tertiary education, a certain percentage of drop-outs can be expected. In this instance, the authors were interested in the abandonment or withdrawal of students from the Diploma in General Nursing at Greys Hospital, Pietermaritzburg. Over the past few years the drop out rate at Greys Hospital was sufficiently high to cause concern - particularly at a time when there is a widely reported shortage of White nursing personnel. Also, in the South African context, very little active research has been reported in this regard.